2013
DOI: 10.1021/jp406817k
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Hydrophilicity of Anatase TiO2 Surfaces by Deposition of Alkaline Earths: The Case of Ca

Abstract: We show with DFT calculations within the COSMO framework that the wetting energy of clean or hydroxylated anatase TiO2 surfaces is strongly enhanced by Ca deposition at low coverage. Two mechanisms contribute to this behavior: the ionic character of Ca adsorption and the inhomogeneity of the transferred charge density, leading together to a strong polarization of the embedding medium. In turn, this polarization is responsible for a large wetting energy and the predicted hydrophilicity. By increasing coverage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Because the above-mentioned surfaces exhibit similar roughness and topography, the grain size and surface chemistry would be responsible for their different hydrophilicity. The improvement in the hydrophilicity of Ca-implanted surfaces in this work is consistent with the result reported by Posternak et al 29 They fabricated a Ca layer on the anatase surface by metal vapor deposition and attributed the signicant enhancement in wettability of the modied surface to enhanced polarization. In addition, the Ca-implanted samples usually possess unique surface characteristic.…”
Section: Surface Roughness Contact Angle and Xps Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…Because the above-mentioned surfaces exhibit similar roughness and topography, the grain size and surface chemistry would be responsible for their different hydrophilicity. The improvement in the hydrophilicity of Ca-implanted surfaces in this work is consistent with the result reported by Posternak et al 29 They fabricated a Ca layer on the anatase surface by metal vapor deposition and attributed the signicant enhancement in wettability of the modied surface to enhanced polarization. In addition, the Ca-implanted samples usually possess unique surface characteristic.…”
Section: Surface Roughness Contact Angle and Xps Analysissupporting
confidence: 92%
“…30 Calcium hydroxide is reported to be able to induce a larger amount of active hydroxyl radicals on Ca-implanted Ti than on non-implanted Ti; 31,32 this hydroxylation would be very helpful for improving the surface hydrophilic properties of the Ca-implanted surfaces. 29 In this work, we also examined the chemical states of the elements on the Ca-ion and Ca/Ag dual-ion implanted surfaces by obtaining high-resolution XPS spectra of Ca 2p, Ti 2p and O 1s, which are shown in Fig. 3(c).…”
Section: Surface Roughness Contact Angle and Xps Analysismentioning
confidence: 99%
“…Generally, the electronic properties of those modified implant surfaces play a dominant role in their performances. And the first principles calculations, as a kind of widely used method to simulate the electronic structure of materials, could provide microscopic descriptions of some relevant processes of various materials . In recent years, researchers began trying new material design and surface modification methods by the first principles method.…”
Section: Introductionmentioning
confidence: 99%
“…And the first principles calculations, as a kind of widely used method to simulate the electronic structure of materials, could provide microscopic descriptions of some relevant processes of various materials. [10][11][12][13] In recent years, researchers began trying new material design and surface modification methods by the first principles method. Yang et al [14] investigated the function of alkaline earth metal oxides (BaO, SrO, CaO, MgO) for TiO 2 catalysts used in CO oxidation from experiments and calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Such a study would be an essential step towards a more thorough understanding of the system, leading to the optimization of many related applications. As an example, it was recently demonstrated that a low surface calcium coverage may increase the wetting energy and therefore the surface hydrophilicity of TiO 2 surfaces [ 17 ]. This has very interesting implications for the application of Ti-based biomaterials, since the augmented wettability would enhance the interaction between the implant surface and the biological environment.…”
Section: Introductionmentioning
confidence: 99%